The Role of Akidah Akhlak Teachers in Shaping the Praiseworthy Morals of Student - Nursyam; Samintang; Muhammad Sarib Abdul Razak; Rusli Takunas; Elya; Nurhanifah (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
Education is the main foundation in shaping the character of a civilization and determining the direction of a nation's development. However, over time, the entry of the globalization era in the world of education brings various problems and challenges. The main problem faced by the world of education in the era of globalization is moral decline. This study aims to look at and examine the role of akidah akhlak teachers in shaping the praiseworthy morals of grade VI students at MI Alkhairaat Biromaru, Sigi Regency. This research uses qualitative field research methods using Miles and Huberman data analysis. The results showed that the teacher of akidah akhlak in class VI MI Alkhairaat Biromaru played a role in shaping the praiseworthy morals of students. The role played by the moral character teacher in class VI MI Alkhairaat Biromaru includes the role of the teacher as a motivator, inspirer, demonstrator, corrector, mentor, and evaluator. The various roles are implemented in providing material and exemplary practices. The results of this study confirm previous research that moral creed teachers play a role in shaping the morals of students. This research is limited to the object of research which only focuses on the Madrasah Ibtidaiyah level.